Evaluating a culturally relevant, low-cost Snakes and Ladders game to strengthen mother-child attachment: a pre-experimental study - Juli Oktalia; Risha Hardina; Yulia Sari; Debbiyantina Debbiyantina; Shentya Fitriana (Healthcare in Low-resource Settings, 2025)
A mother’s role is crucial in meeting the physical and psychological needs of her child, such as affection, love, and attention. By leveraging a culturally relevant and interactive medium, this study examined how shared play experiences foster emotional connections and strengthen family bonds. It examines the use of a low-cost, modified Snakes and Ladders game to improve mother-child attachment, focusing on the caregiving practices of mothers who rarely engage in beneficial play activities. A pre-experimental design with a one-group pretest-posttest design was employed, with 160 respondents selected through stratified random sampling. The data were analyzed using a paired-sample t-test. The analysis revealed a significant increase in attachment (p<0.000). The game encouraged structured, enjoyable interactions that promoted communication, cooperation, and emotional closeness between mothers and their children. The modified Snakes and Ladders game is an effective tool for enhancing mother-child attachment by fostering mutual support, understanding, and trust. However, this study is limited by its pre-experimental design, which lacks a control group, and its focus on a specific age group and cultural context. Future research could explore the impact of the game in diverse settings and with different populations to validate its broader applicability. These findings suggest the potential for culturally relevant, low-cost games to be integrated into parenting interventions to strengthen familial relationships.